GAMBARAN PENGETAHUAN DOKTER GIGI TENTANG REKAM MEDIK GIGI - Murniwati Murniwati; Rizanda Machmud; Suci Rahmasari (Andalas Dental Journal, 2013)
Dental records must comply with National Standard of Dentistry, Medical Record must contain data that identity of the patient, patient's general condition, odontogram, dental care data and the name and signature of the dentist and dental records are more important filled completely. This study aim to know the knowledge of all dentists in Padang to dentall record. The design of this study is Descriptive. The populations in this study were all dentists who working in health centers and hospitals of Padang. The sampling technique is Total Sampling and data collection through questionnaires and observation of dental records. The results showed that the rate of the level of knowledge about the importance of dentall record low according to national standards where knowledge about medikolegal aspects is the subject to a level of knowledge is low, reaching only 4.2%. Knowledge of dentists about the medical records dental national standards is low because of the lock of socialization and conducted a related-party factor. It could be need to socialization and provide the policy of dental record based on national standard for all dentists.